2005
DOI: 10.1002/pse.202
|View full text |Cite
|
Sign up to set email alerts
|

Beams and plates on elastic foundations: a review

Abstract: The interaction action between structures and supporting soil media is of fundamental importance in foundation design and it has always attracted the attention of both researchers and engineers. This paper reviews the state-of-the-art in this field, highlighting the key areas of development, including the modelling of the soil media and various analytical as well as numerical approaches in analysing the interaction action between the foundation and soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(76 citation statements)
references
References 87 publications
(101 reference statements)
1
69
0
6
Order By: Relevance
“…Amongst the prevailing models, the most diffused one considers the train vehicle as a single load traveling at constant velocity on a beam supported by an elastic foundation (see Kerr [13]). Comprehensive literature reviews about the problem of moving loads acting on beams may be found in Beskou and Theodorakopoulos [2], Frýba [11], Kerr [13] and Wang et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the prevailing models, the most diffused one considers the train vehicle as a single load traveling at constant velocity on a beam supported by an elastic foundation (see Kerr [13]). Comprehensive literature reviews about the problem of moving loads acting on beams may be found in Beskou and Theodorakopoulos [2], Frýba [11], Kerr [13] and Wang et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Following a different approach, Cheung and Nag (1968;Wang et al, 2005) substituted piecewise constant tractions into Equation 7a and 7b and directly used those equations to obtain horizontal and vertical displacements of the substrate boundary, respectively. Such an approach assumes the presence of a finite number of equally spaced links between the foundation beam and the substrate.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…However, in order to ensure null displacements at the boundaries, the substrate mesh must be extended far away from the loaded area, often involving a huge number of FEs and a discouraging computional effort. To improve the numerical efficiency, infinite elements were proposed (Wang et al, 2005). The use, in the FE Method (FEM), of classical beam models for the foundation and of two-dimensional FEs for the soil makes to lose the continuity of rotations at the substrate boundary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the review [1], devoted to this subject matter, considers the items of elastic foundations development models, as well as various approaches to analytical and numerical investigation of beams and plates with elastic foundations interaction. Reference [2] studies free and forced oscillations of a circular plate, the plate resting on Winkler foundation.…”
Section: Introductionmentioning
confidence: 99%